Race, ideology, and the decline of Caribbean Marxism - Maingot, Anthony P. (University Press of Florida, 2015)
In this book, Anthony Maingot examines the contemporary intellectual, social, economic, and cultural trajectories of Caribbean nations in light of the challenges the region as a whole has faced in the postcolonial era. By focusing on changes since the 1990s in the context of intellectual roots and movements of the past, this manuscript helps define the future course of studies in the field with regard to an empirically-valid, coherent assessment of a complex region.